2022
DOI: 10.5829/ije.2022.35.11b.05
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Stress-strain Relationships for Recycled Aggregate Concrete

Abstract: There is a growing demand of suitable substitute materials of concrete ingredients especially fine and coarse aggregates in order to achieve sustainable development in the era of rapid urbanisation. Therefore, the concrete making process by utilisation of aggregates that recycled from construction and demolition (C&D) debris has emerged as a primary objective for many government agencies. Consequently, the utilisation of recycled aggregate concrete (RAC) in structural applications become essential aspect. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…The average of two beams is reported in Table 5. This result indicates slightly inferior than NAC, but considerable behaviour of RAC beam in torsion as found in the literature [2][3][4][5].…”
Section: Effect Of Rca On Torsional Strengthsupporting
confidence: 79%
See 3 more Smart Citations
“…The average of two beams is reported in Table 5. This result indicates slightly inferior than NAC, but considerable behaviour of RAC beam in torsion as found in the literature [2][3][4][5].…”
Section: Effect Of Rca On Torsional Strengthsupporting
confidence: 79%
“…Because RAC has an inferior elastic modulus than NAC and the twist angle of beams at every loading state increases as the ratio of RCA was increased. Similar torsional behaviour was mentioned `in the experimental work [4,5]. Table 5 summarized data when RCA grows, the cracking torque to ultimate torque capacity decreases.…”
Section: Effect Of Rca On Torsional Strengthsupporting
confidence: 78%
See 2 more Smart Citations
“…RAC beams have better performance than NAC beams, and they can be used as structural concrete [20]. The utilization of RAC in structural applications has become an essential aspect in recent studies [21]. The experimental examination of RAC beams demonstrated that altering the amount of RCA in RAC had no effect on structural behavior [22,23].…”
Section: Introductionmentioning
confidence: 99%